Os princípios de psicologia de William James: compromissos e consequências de uma filosofia da ação - Bertoni, Paulo Gilberto (2011)
This work analyzes the psychological texts of William James (1842-1910), specially his Principles of Psychology, published in 1890. We begin following an alternative itinerary of reading proposed by James in the preface of the book, which also allows us to understand how the New Psychology has influenced the construction of psychological field in 19th century. We present this in our first chapter trying to show what we call a theory of action. In the second chapter, the previous conclusions are articulated with James exposition of the thought as a stream and with his considerations of the Self. In the third, we investigate the relations between his psychology of cognition and his posterior epistemology. Finally, we postulate that The Principles must be understood as a psychology of action, which has its basis in a philosophy of action incorporated, consciously or not, by James. We emphasize onward the research the tension created between the dualistic point of view assumed by James and the conclusions suggested by a closer reading.